Effect of simplifying the body model to compute the energy parameters in pole vaulting - Frère, J.; Sanchez, H.; Vanhaesebrouck, R.; Cassirame, J. (Sports Biomechanics, 2021)
This study compared changes in the energy-time profiles in pole vaulting using several body models. Two-dimensional kinematics were collected from 20 successful vaults (5.20-6.01 m) performed by 10 athletes during a national meet. The linear and angular kinetic, potential, and total mechanical energy-time profiles were obtained from three pole vaulter models composed of 12, 5, and 3 segments (M12, M5, and M3, respectively), as well as calculated and approximated centre of mass models. One-dimensional statistical parametric mapping was used to compare these energy-time profiles from the models, while agreements of discrete energy parameters were assessed. For all the studied energy-time profiles, there was a main effect (0.05 < p < 0.001) of the models, but pairwise comparisons showed that M5 presented the lowest differences with M12 in comparison with the other models (M3 and approximated centre of mass models). In addition, M5 showed better agreement (lower bias and small effect size) with M12 for the studied energy parameters compared to the other models. Therefore, M5 may be a reliable option to simplify the body model and speed up the computation of the energy-time profiles of the pole vaulter.